1994
DOI: 10.1111/j.1365-2249.1994.tb06580.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T lymphocyte activity and CD8 subpopulations in children at risk of HIV infection

Abstract: SUMMARYHIV-specific cytotoxic T lymphocytes (CTL) are thought to play a major role in viral control in HIV-infected adults. Changes in the relative proportions of CDS lymphocyte subpopulations are also thought to be associated with disease progression. Less is known about the relative effectiveness of CTL against different HIV targets, or about the relationship, if any. between CTL activity and CDS subpopuiations. We have measured CTL activity against four HIV gene products (gag. tat. pal and en\) and expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…We found that 45% of infants were able to generate cellular immune responses of substantial breadth and magnitude; however, most responses were transient. Our finding confirms previous studies that detected responses in HIV-1 EU infants [22,27,28,31], and is consistent with our previous study that observed 47% prevalence of at least one positive ELISPOT assay using human leucocyte antigen (HLA)-matched peptide stimulation in breastfeeding EU infants [29]. We also found significant associations between maternal plasma and breastmilk HIV-1 viral levels and infant magnitude of HIV-1-specific ELISPOT responses, suggesting that antigen exposure modifies the induced infant HIV-1-specific immune responses.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that 45% of infants were able to generate cellular immune responses of substantial breadth and magnitude; however, most responses were transient. Our finding confirms previous studies that detected responses in HIV-1 EU infants [22,27,28,31], and is consistent with our previous study that observed 47% prevalence of at least one positive ELISPOT assay using human leucocyte antigen (HLA)-matched peptide stimulation in breastfeeding EU infants [29]. We also found significant associations between maternal plasma and breastmilk HIV-1 viral levels and infant magnitude of HIV-1-specific ELISPOT responses, suggesting that antigen exposure modifies the induced infant HIV-1-specific immune responses.…”
Section: Discussionsupporting
confidence: 93%
“…HIV-1-specific cellular immune responses have been reported in varied HIV-1 EU populations, including commercial sex workers [15][16][17], HIV-1-discordant couples [18][19][20] and infants born to HIV-1-infected women [21][22][23]. CD4 1 and CD8 1 HIV-1-specific responses have been observed in EU infants, with prevalence ranging from 3 to 56% [24][25][26][27] and 0 to 47% [22,[27][28][29][30][31], respectively, resulting in controversy around the detection of these responses and their potential protective role. However, vaccine development relies upon understanding the induction of immune responses, and so it remains important to identify the correlates of presence and magnitude of HIV-1specific immune responses in EU individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by our group and others in perinatal HIV-exposed infants have reported evidence of HIV-specific immune response (4,(18)(19)(20)(21)(22)(23)(24)(25). HIV-specific immune response has also been observed in exposed noninfected adults (26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 57%
“…However, in the study by Betts et al, variations in the number of HIVspecific CD8 + T-cell in chronically infected patients were in much broader ranges -between 1.6 and 18.4% of total CD8 + T-cells [83]. HIV-1-specific CD8 + CTLs in HIV-1-infected children have frequency and specificity similar to those found in HIV-1-infected adults [84][85][86]. Frequencies of SIV-and HIV-1-specific T-cells are not the sole determinants of immunemediated protection in viral infection [83].…”
mentioning
confidence: 85%